2003
DOI: 10.1542/peds.111.6.1312
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Health Among Young Victims and Offenders of Direct and Indirect Bullying

Abstract: Bullying Psychosocial Health Among Young Victims and Offenders of Direct and IndirectParticipants. A total of 4811 children aged 9 to 13. Results. Depression and suicidal ideation are common outcomes of being bullied in both boys and girls. These associations are stronger for indirect than direct bullying. After correction, direct bullying had a significant effect on depression and suicidal ideation in girls, but not in boys. Boy and girl offenders of bullying far more often reported delinquent behavior. Bully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
217
2
17

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(252 citation statements)
references
References 25 publications
16
217
2
17
Order By: Relevance
“…Most studies of differences in bullying by sex from around the world also found a higher rate of victimization among boys than in girls [1,2]. This may be due to boys experiencing more direct bullying such as verbal and physical attacks while girls experience indirect bullying such as social exclusion or the spread of rumours; in addition "indirect" bullying may be less likely to be reported [21]. Peer victimization increased with age in Egypt and did not change with age in the other 3 study countries.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of differences in bullying by sex from around the world also found a higher rate of victimization among boys than in girls [1,2]. This may be due to boys experiencing more direct bullying such as verbal and physical attacks while girls experience indirect bullying such as social exclusion or the spread of rumours; in addition "indirect" bullying may be less likely to be reported [21]. Peer victimization increased with age in Egypt and did not change with age in the other 3 study countries.…”
Section: Discussionmentioning
confidence: 99%
“…3 Negative actions can be classified as direct or indirect forms of aggression that cause harm to the victim. 4 The definition of bullying has been reported to vary according to the age of the child, 5 between teachers and adolescents 6,7 and due to variations Bullying in school-aged children is a global phenomenon. The effects of bullying can be both short-and long-term, resulting in both physiological and psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Some victims of bullying have committed suicide. Children as young as nine may think about suicide as a way to escape their bullies [5]. Victims had significantly higher scores on depressive thoughts.…”
Section: Background Of Studymentioning
confidence: 99%